Electronic Notarial Deed Register Book (Repertorium) In The Digital Era - Latifah Latifah; Suprapto Suprapto (Fakultas Hukum Dehasen, 2024)
This study aims to explain and analyze the legal regulations concerning the electronic storage of Act Register Books (Repertorium) under Indonesian law. The research employs normative legal research methods, using a statute approach to examine legal rules related to the electronic storage of documents and a conceptual approach to understand the Cyber Notary concept when specific regulations are not yet available. The sources of legal materials include laws, regulations, books, journals, and dictionaries, with data collection conducted through inventory and literature review, and qualitative analysis. The findings indicate that the legal framework for the electronic storage of documents within the Cyber Notary concept in Indonesia remains unclear. While Law No. 11 of 2008 on Electronic Information and Transactions provides general regulations for electronic documents, there is no specific provision for notarial protocols. Notaries must ensure the validity and security of electronic documents through certification services, secure repositories, and sharing services. This research contributes to a deeper understanding of the legal framework for electronic document storage and offers practical insights into the legal and technical implications within the Cyber Notary context.